Payment delay in supply chain management: a systematic literature review. (8th April 2021) - Eddine, Mohamed Hicham Salah; Saikouk, Tarik; Berrado, Abdelaziz
There is a general agreement in the literature that the payment delay (PD) is one of the strongest reasons for business failures nowadays. This paper studies PD in supply chain management (SCM) literature by providing a systematic literature review (SLR) of exclusively high ranked journals in the field of operation management. The authors identified five major issues in supply PD, namely inventory, cash flow, financial decision, supply chain (SC) coordination, and demand. They also discerned a growing trend in the literature related to analytical studies, which limits the generalisation of the findings, mostly due to the various assumptions used in the modelling process. The majority of these papers focused on the retail field because of its coordinated structure. This paper suggests that PD, as a coordination tool, can improve both the supplier's and retailer's profit. The paper concludes by suggesting a conceptual framework that summarises how PD influences the issues addressed above. The authors pinpoint potential future areas such as simulation under dynamic scenarios, including multi-echelon partners in order to better gauge the impact of PD on SC performance.